Carbon-based supported nano manganese-iron-copper catalyst and preparation method and application thereof
By depositing manganese, iron and copper elements on carbon-based support, carbon-based supported nano-ferromanganese copper catalysts were prepared, which solved the problems of low activity, high cost and short life of the existing catalysts, and achieved efficient catalytic degradation and long-term use of foul-odor organic waste gas.
Patent Information
- Application Number
- CN202411790693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-04
AI Technical Summary
Existing catalysts have low activity, high cost and short life in the treatment of foul-odor organic waste gas, and polymetallic catalysts are insufficiently used in catalytic degradation of foul-odor organic waste gas.
The plasma method is used to deposit elements such as manganese, iron, and copper on the carbon-based support to prepare a carbon-based iron-manganese copper catalyst, and the catalytic degradation efficiency is improved through the synergistic action of manganese, iron and copper.
It realizes efficient catalytic degradation of foul-odor organic waste gas, and the catalyst has good dispersion, thermal stability and electrocatalytic properties, with a high degradation rate and a long life, reducing operating costs.
Smart Images

Figure BDA0005175242690000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and more specifically, relates to a carbon-based supported nano manganese iron copper catalyst and a preparation method and application thereof. Background Art
[0002] Malodorous organic waste gas emissions are a common source of pollution in many industrial processes, such as wastewater treatment, plastic manufacturing, pulp and paper industry, etc. Malodorous organic waste gas often contains harmful gases such as ammonia, hydrogen sulfide, toluene, formaldehyde, volatile organic compounds (VOCs), etc., which seriously affect environmental quality and public health.
[0003] In the prior art, photocatalytic technology, adsorption technology, chemical oxidation and other methods have been widely used in the treatment of malodorous organic waste gas. However, these technologies have certain limitations, such as low catalyst activity, high cost, short catalyst life and other problems. Therefore, the development of a catalyst system with high activity, low cost and long-term effectiveness has become a hot topic in current research. For example, the patent with patent publication number CN104815614A discloses a method for preparing iron-loaded activated carbon, which adopts an impregnation method to immerse the activated carbon in an impregnation solution containing iron salts, and then dries it in nitrogen to obtain a carrier activated carbon. However, it still has problems such as low catalyst activity and short catalyst life.
[0004] In addition, the catalysts used for the catalytic degradation of malodorous organic waste gas are often transition metals or multiple catalysts used together. For example, the patent publication number CN105107521A discloses a Mn-Fe bimetallic doped activated carbon-based desulfurization catalyst, which also adopts the impregnation method, uses nitric acid-modified activated carbon as a carrier, and uses metal Mn and Fe as active components to prepare a Mn-Fe bimetallic doped activated carbon-based catalyst. However, the scheme only discloses its application as a desulfurization catalyst, and there is no relevant research on the catalytic degradation of malodorous organic waste gas.
[0005] Therefore, how to provide a catalyst based on multiple metals that has excellent catalytic degradation effect on malodorous organic waste gas has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a method for preparing a carbon-based supported nano manganese iron copper catalyst. The prepared carbon-based supported nano manganese iron copper catalyst has an excellent catalytic degradation effect on odorous organic waste gas.
[0007] The second object of the present invention is to provide a carbon-based supported nano manganese iron copper catalyst prepared by the above preparation method.
[0008] The third object of the present invention is to provide a use of a carbon-based supported nano manganese iron copper catalyst in catalytic degradation of malodorous organic waste gas.
[0009] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0010] The present invention claims a method for preparing a carbon-based supported nano manganese iron copper catalyst, comprising the following steps:
[0011] S1. Mixing an iron source, a manganese source, a copper source, a carbon source and a solvent, and dispersing them uniformly to prepare a precursor solution;
[0012] S2. Under the protection of a protective gas, the precursor solution in step S1 is treated by a plasma method and post-treated to obtain the carbon-based nano-manganese iron copper catalyst;
[0013] The plasma treatment conditions are: temperature of 1500-3000° C., current of 100-300A, protective gas flow of 5-20L / min, and pressure of 0.1-1.5atm.
[0014] The present invention provides a method for preparing a carbon-based supported nano manganese iron copper catalyst. Elements such as manganese, copper and iron are deposited on a carbon-based carrier by a plasma method to prepare a carbon-based supported nano manganese iron copper catalyst.
[0015] In the present invention, the active components are combined with manganese, iron and copper, which can play a synergistic role in improving the catalytic degradation of malodorous organic waste gases. Specifically, manganese, iron and copper can provide different active sites in the reaction and increase the number of active centers of the catalytic reaction. In the degradation of malodorous organic waste gases, manganese, iron and copper interact with pollutants together. Manganese appears in an oxidized state in the reaction, and iron maintains the balance of the reaction by switching between +2 and +3 valences. At the same time, manganese and iron can promote the Fenton reaction to generate free radicals to effectively degrade organic waste gases. The addition of copper enhances the catalyst's ability to degrade a variety of malodorous organic waste gases. At the same time, copper can change the path of some catalytic reactions and promote specific reactions, such as the degradation of alcohols, ketones and aromatic hydrocarbons. Copper, as a good conductive material, can improve the electron transfer ability of the catalyst, and the catalyst containing copper has a better regeneration ability when facing toxic substances and pollutant deposition.
[0016] Further, the present invention adopts a plasma method to prepare a catalyst, which can increase the dispersibility of active components and carriers, thereby increasing the specific surface area, and the plasma method can improve the structure and morphology of the catalyst, promote the synthesis of substances, enhance the catalytic activity and stability, and be environmentally friendly. The plasma method can make Mn, Fe, and Cu present in a nano state and load on a carbon-based carrier. For nanoparticles, in terms of specific surface area, the nanoparticles have a small particle size and a large specific surface area, and more active sites are exposed, which can increase the probability of contact with malodorous organic waste gas and improve the catalytic reaction rate. In terms of catalytic activity, the nano state shortens the diffusion distance of the reactants, reduces the activation energy of the reaction, and can accelerate the adsorption, desorption and conversion of the reaction molecules, so that the catalytic degradation is carried out efficiently. In terms of stability, nano-state Mn, Fe, and Cu interact strongly with carbon-based carriers, prevent metal agglomeration and sintering, ensure a highly dispersed stable structure, maintain activity after multiple catalytic cycles, extend the life of the catalyst, ensure long-term and efficient operation in the treatment of malodorous organic waste gas, reduce costs, and have strong applicability.
[0017] Furthermore, the inventors have found through research that when the catalyst is prepared by the plasma method, the carbon-based supported nano manganese iron copper catalyst prepared by using a specific reaction temperature, current, gas flow rate and pressure has an excellent degradation effect. When the reaction temperature is low, the metal cannot be nanosized; when the reaction temperature is high, it will cause the metal particles to sinter, thereby reducing the dispersibility and catalytic activity of the active components. If the current is too low, it will lead to insufficient plasma energy, Mn, Fe, and Cu are difficult to nanosize, large particle size, poor dispersion, few active sites, and limited contact with odorous organic waste gas; if the current is too high, the metal particles are easy to sinter and agglomerate, lose high dispersion characteristics, shrink specific surface area, reduce active sites, and hinder the adsorption and conversion of reactants. Appropriate gas flow helps the precursor solution to mix and disperse in the plasma environment, and the energy distribution of the plasma is more stable, so that the active components are evenly distributed on the carbon source. The evenly dispersed active components and stable structure help to increase the number and accessibility of active sites; it helps to regulate the chemical state and crystal structure of the active components. However, if the gas flow rate is too low, the local energy will be abnormal (too high or too low), and the active components will be unevenly distributed on the carbon source, resulting in agglomeration. As for the pressure selection, if the pressure is too low, the plasma density will be reduced, the energy will be insufficient, and the catalyst loading and the distribution of active components will be affected. If the pressure is too high, small particles will agglomerate, and the specific surface area of the catalyst will be reduced. The appropriate pressure helps to maintain the state of the plasma, so that the active components can effectively interact with the carbon source, and it helps to stabilize the structure of the prepared catalyst.
[0018] Preferably, in step S2, the temperature of the plasma method is 2000-2800° C. More specifically, the temperature may be 1600° C., 1700° C., 1800° C., 1900° C., 2000° C., 2100° C., 2200° C., 2300° C., 2400° C., 2500° C., 2600° C., 2700° C., 2800° C., 2900° C., etc., or an interval range formed by any of the above values, such as 1500-2600° C., 2000-2800° C., 2400-2900° C., etc., but the present invention is not limited thereto.
[0019] Preferably, in step S2, the current of the plasma method is 150-250 A. Further preferably, the current of the plasma method is 180-220 A. More specifically, the current can be 120A, 140A, 160A, 180A, 200A, 220A, 240A, 260A, 280A, 300A, etc., or an interval range formed by any of the above values, such as 120-180A, 160-280A, 220-300A, etc., but the present invention is not limited thereto.
[0020] Preferably, the protective gas flow rate is 12-16 L / min. More specifically, the protective gas flow rate can be 7 L / min, 9 L / min, 11 L / min, 13 L / min, 15 L / min, 17 L / min, 19 L / min, etc., or an interval range formed by any of the above values, such as 7-9 L / min, 9-15 L / min, 12-18 L / min, etc., but the present invention is not limited thereto.
[0021] Preferably, the pressure is 0.8-1.2 atm. More specifically, the pressure can be 0.3 atm, 0.5 atm, 0.7 atm, 0.9 atm, 1.1 atm, 1.3 atm, etc., or an interval formed by any of the above values, such as 0.3-1.1 atm, 0.3-1.3 atm, 0.8-1.5 atm, etc., but the present invention is not limited thereto.
[0022] Preferably, the mass ratio of the iron source, manganese source, copper source and carbon source is 1-3: 1-3: 1-3: 1-3. Further preferably, the mass ratio of the iron source, manganese source, copper source and carbon source is 1: 1: 1: 2. Under this preferred condition, manganese, iron and copper have better dispersibility and are evenly dispersed on the carbon source, so that the prepared carbon-based supported nano manganese iron copper catalyst has a better catalytic degradation effect.
[0023] Preferably, the manganese source is selected from one or more of MnO2, MnCl2, Mn(NO3)2, and MnCO3.
[0024] Preferably, the copper source is selected from one or more of CuSO4, CuCl2, and Cu(NO3)2.
[0025] Preferably, the iron source is selected from one or more of Fe(NO3)3, Fe2(SO4)3, and FeCl3.
[0026] Preferably, the carbon source is selected from one or more of activated carbon, graphite, carbon nanotubes, and graphene. Further preferably, the carbon source is activated carbon. Specifically, the specific surface area of the activated carbon is 1000-1200 m 2 / g, and the average particle size is 3-5μm.
[0027] Preferably, in step S1, rare earth or its oxide is also added. Further, rare earth or its oxide can play a role in improving the activity of the catalyst, stabilizing the catalyst structure, promoting the generation of free radicals, and improving the adsorption capacity. Further preferably, the type of the rare earth is one or more of La, Ce, Pr, Nd, and Sm. Further preferably, when there are multiple types of rare earth, the mass ratio between any two of them is 1:(0.5-2).
[0028] Further preferably, the mass ratio of the iron source to the rare earth or its oxide is 1-3:0.1-2.
[0029] Preferably, the plasma is generated by an arc furnace, a high-frequency power supply, a laser, a radio frequency or a microwave. Further preferably, the plasma is an arc plasma generated by an arc furnace. The high-energy ions generated by the arc furnace contribute to the nano-sizing of the catalyst, which can increase the specific surface area and active sites of the catalyst, thereby enhancing the catalytic performance, and the plasma energy density generated by the arc furnace is greater, and it is easier to form active sites on the surface of the carrier. The arc plasma generated by the arc furnace has a higher plasma temperature and energy density, can fully activate metal ions, can effectively improve the reaction rate and efficiency in terms of gas flow, composition and temperature, etc., and makes the optimization design of the corresponding catalyst more flexible.
[0030] Preferably, the solvent is an alcohol solvent, including but not limited to ethanol and the like.
[0031] Preferably, the protective gas is an inert gas, including but not limited to argon gas.
[0032] Preferably, the post-treatment includes one or more of cooling, washing and drying. The post-treatment is performed to remove impurities in the product.
[0033] In some embodiments, as a preferred embodiment of the present invention, the detergent used for washing can be at least one of ethanol and deionized water.
[0034] In some embodiments, as a preferred embodiment of the present invention, the drying conditions are: temperature 100-120° C., time 2-4 h.
[0035] Furthermore, the present invention seeks to protect the carbon-based supported nano manganese iron copper catalyst prepared by the above preparation method.
[0036] Furthermore, the present invention seeks to protect the use of the above-mentioned carbon-based supported nano manganese iron copper catalyst in catalytic degradation of malodorous organic waste gas.
[0037] Preferably, the malodorous organic waste gas is selected from one or more of toluene, formaldehyde, hydrogen sulfide and ammonia.
[0038] Preferably, during catalytic degradation, the mass ratio of the carbon-based supported nano manganese iron copper catalyst to the malodorous organic waste gas is 1: (1-100). More specifically, the catalytic degradation method can be a static reaction or a dynamic reaction. When the carbon-based supported nano manganese iron copper catalyst is placed in the malodorous organic waste gas, the catalyst first adsorbs the pollutants. Since the catalyst uses a carbon-based material as a carrier, the adsorption effect on the organic waste gas is extremely obvious.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention provides a method for preparing a carbon-based nano manganese iron copper catalyst. Elements such as manganese, copper, and iron are deposited on a carbon-based carrier by a plasma method to prepare a carbon-based nano manganese iron copper catalyst. The active components Mn, Fe, and Cu are matched and combined with a specific preparation method to produce a synergistic effect, so that the catalyst has good degradation ability when treating odorous organic waste gas, and can enhance the electrocatalytic performance of the catalyst, thereby improving the degradation efficiency.
[0041] (2) The carbon-based supported nano manganese iron copper catalyst prepared by the present invention exhibits excellent activity in catalytic reactions and can degrade a variety of organic pollutants, and can maintain good activity and catalytic effect even at low and high temperatures.
[0042] (3) For the nano manganese iron copper catalyst, the introduction of the carbon-based carrier in the present invention can improve the dispersibility and thermal stability of the catalyst, and the carbon-based supported nano manganese iron copper catalyst prepared by the arc plasma method can show good tolerance, anti-toxicity, high metal activity and reversibility, which helps the catalyst to maintain activity during repeated use and prolong its service life. The catalyst has a stable structure and can effectively remove sediments and restore catalytic activity after high-temperature treatment. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the specification and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0044] Example 1
[0045] (1) Weigh 10g Fe(NO3)3, 20g activated carbon (specific surface area 1000-1200m 2 / g, average particle size is 3-5μm), 10gMnO2, 10gCuSO4 and 5g rare earth oxide CeO2 (purity ≥99%). First, Fe(NO3)3, MnO2, CuSO4 and CeO2 are placed in a ball mill and ground at 350r / min for 2.5h to form a uniform fine powder. The fine powder is transferred into a three-necked flask, 250mL of ethanol solvent is added, and the mixture is stirred at 55℃ and 300r / min for 4h to obtain a mixed solution. Then, activated carbon is slowly added and stirred for 2.5h to ensure that each substance is fully dispersed and dissolved to obtain a precursor solution.
[0046] (2) An arc furnace was used to prepare arc plasma, argon was selected as the carrier gas, and then the reaction temperature was set to 1500°C, the current was 200A, the argon flow rate was 15L / min, and the pressure was 1atm. The precursor solution was placed in the reaction chamber, and the arc furnace was started to prepare the product. After the product was cooled, it was washed three times with ethanol and deionized water respectively. The product was vacuum dried at 100°C for 2h to obtain a carbon-based supported nano manganese iron copper catalyst, recorded as C-Mn-Fe-Cu nano 1500.
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is that in step (2), the reaction temperature of the electric arc furnace is set to 2000°C.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that in step (2), the reaction temperature of the electric arc furnace is set to 2500°C.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 1 is that in step (2), the reaction temperature of the electric arc furnace is set to 3000°C.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 1 is that in step (2), the arc furnace is set to a reaction temperature of 2500° C. and a current of 100A.
[0055] Example 6
[0056] The difference between this embodiment and embodiment 1 is that in step (2), the arc furnace is set to a reaction temperature of 2500° C. and a current of 300A.
[0057] Example 7
[0058] The difference between this embodiment and embodiment 1 is that: in step (1), 10 g Fe(NO3)3, 30 g MnO2, and 30 g CuSO4 are taken; in step (2), the reaction temperature of the electric arc furnace is set to 2500°C.
[0059] Example 8
[0060] The difference between this embodiment and embodiment 1 is that in step (1), no rare earth oxide is added, and 10g Fe(NO3)3, 10g MnO2, and 10g CuSO4 are taken; in step (2), the reaction temperature of the electric arc furnace is set to 2500°C.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 3 is that in step (1), no CuSO4 is added; 15g Fe(NO3)3 and 15g MnO2 are taken.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 3 is that in step (1), no Fe(NO3)3 is added, and 15g MnO2 and 15g CuSO4 are taken.
[0065] Comparative Example 3
[0066] The difference between this comparative example and Example 3 is that in step (1), no MnO2 is added, and 15g Fe(NO3)3 and 15g CuSO4 are taken.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 1 is that the reaction temperature of the electric arc furnace is set to 1000°C.
[0069] Comparative Example 5
[0070] The difference between this comparative example and Example 1 is that the reaction temperature of the electric arc furnace is set to 3500°C.
[0071] Test Example 1
[0072] Weigh 1.00g of the catalyst prepared in the embodiment and the comparative example, and fill it into a quartz tube with an inner diameter of 6mm. The rest of the tube is filled with quartz sand. The quartz tube is placed in a tubular resistance furnace, and the gas flow rate is controlled to be 100mL / min, wherein the flow rate of N2 with toluene is 8mL / min, the air flow rate is 92mL / min, the toluene content in the mixture is controlled to be 1000ppm, and the toluene reflux water temperature of the thermostatic water tank is 5°C. The activity test is carried out using a PE gas chromatograph, an FID detector, and a KB-1 capillary chromatographic column (30mm×0.25mm×0.25mm), and the reaction temperature is 220°C for 30min. The test results are shown in Tables 1 and 2.
[0073] Table 1
[0074] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Degradation rate (%) 83 89 98 85 83 90 88 90
[0075] Table 2
[0076] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Degradation rate (%) 80 70 75 50 40
[0077] It can be seen from the above examples that the catalyst prepared by the present invention has an excellent degradation effect on toluene, and the degradation rate is ≥83%; more preferably, the degradation rate is ≥88%; most preferably, the degradation rate is 98%.
[0078] It can be seen from Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 that when the catalyst contains manganese, copper and iron elements at the same time, the prepared catalyst has a better degradation effect, while when only two of the metal combinations are used, it is difficult to achieve the technical effect of the present invention.
[0079] It can be seen from Example 1, Comparative Example 4 and Comparative Example 5 that when the reaction temperature is low or high, it is difficult to achieve the technical effect of the present invention.
[0080] Test Example 2
[0081] Low temperature experiment (-20℃) Experiment: Simulate the treatment of exhaust gas in a cold environment. Take 1.00g of the catalyst prepared in Example 3 and Comparative Example 1, respectively, fill them into a quartz tube with an inner diameter of 6mm, fill the rest with quartz sand, and put them into a low temperature reaction box and a tubular resistance furnace combination device. Control the N2 toluene flow rate to 8mL / min, the air flow rate to 92mL / min, the toluene concentration to 1000ppm, the reaction temperature to -20℃, and the reaction time to 60min. Detect by PE gas chromatography, etc.
[0082] Test results: The degradation rate of toluene for the catalyst prepared in Example 3 under low temperature experiment is 75%, which is 23.5% lower than that when the reaction temperature is 220°C. The degradation rate of toluene for the catalyst prepared in Comparative Example 1 under low temperature experiment is 40%, which is 50% lower than that when the reaction temperature is 220°C. It can be seen that the catalyst prepared in the present invention shows excellent activity in the catalytic reaction and can maintain good activity and catalytic effect at low temperature.
[0083] Test Example 3
[0084] High temperature experiment (400°C): Simulating the industrial high temperature exhaust gas scene, 1.00g of the catalysts prepared in Example 3 and Comparative Example 1 were placed in a quartz tube and placed in a high temperature reactor. The N2 toluene flow rate was controlled to be 8mL / min, the air flow rate was 92mL / min, the toluene concentration was 1000ppm, the reaction temperature was 400°C, and the reaction time was 60min. Detection was performed using PE gas chromatography.
[0085] Test results: The degradation rate of toluene for the catalyst prepared in Example 3 under low temperature experiment is 90%, which is 8.2% lower than that when the reaction temperature is 220°C. The degradation rate of toluene for the catalyst prepared in Comparative Example 1 under low temperature experiment is 55%, which is 31.3% lower than that when the reaction temperature is 220°C. It can be seen that the catalyst prepared in the present invention shows excellent activity in the catalytic reaction and can maintain good activity and catalytic effect at high temperature.
[0086] Test Example 4
[0087] Stability cycle experiment: 1.00 g of the catalyst prepared in Example 3 and Comparative Example 1 were taken and placed in a quartz tube with an inner diameter of 6 mm and filled with quartz sand. The flow rate of toluene with N2 was controlled to be 8 mL / min, the flow rate of air was 92 mL / min, the concentration of toluene was 1000 ppm, and the reaction temperature was 220°C for 30 min, which was one cycle. There were 10 cycles in total, and the degradation rate was tested for each cycle. The degradation effect is shown in Table 3 below.
[0088] Table 3
[0089]
[0090] As shown in Table 3, the degradation rate of the catalyst prepared by the present invention is still 95% after 10 cycles, which is almost unchanged compared with the initial degradation rate. The degradation rate of the catalyst prepared in Comparative Example 1 is 70% after 5 cycles, and only 60% after 10 cycles, which is 25% lower than the initial degradation rate. It can be seen that the catalyst prepared by the present invention has better cyclic stability.
[0091] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A method for preparing a carbon-based supported nano manganese iron copper catalyst, characterized in that: The steps include: S1. Mixing an iron source, a manganese source, a copper source, a carbon source and a solvent, and dispersing them uniformly to prepare a precursor solution; S2. Under the protection of a protective gas, the precursor solution in step S1 is treated by a plasma method and post-treated to obtain the carbon-based nano-manganese iron copper catalyst; The plasma treatment conditions are: temperature of 1500-3000° C., current of 100-300A, protective gas flow of 5-20L / min, and pressure of 0.1-1.5atm.
2. The preparation method according to claim 1, characterized in that: In the step S2, the temperature of the plasma method is 2000-2800°C.
3. The preparation method according to claim 1 or 2, characterized in that: In the step S2, the current of the plasma method is 150-250A.
4. The preparation method according to claim 3, characterized in that: In the step S1, rare earth or its oxide is also added.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the iron source to the rare earth or its oxide is 1-3:0.1-2.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the iron source, manganese source, copper source and carbon source is 1-3:1-3:1-3:1-3.
7. The preparation method according to claim 1, characterized in that: The manganese source is selected from one or more of MnO2, MnCl2, Mn(NO3)2, and MnCO3; the copper source is selected from one or more of CuSO4, CuCl2, and Cu(NO3)2; the iron source is selected from one or more of Fe(NO3)3, Fe2(SO4)3, and FeCl3; the carbon source is selected from one or more of activated carbon, graphite, carbon nanotubes, and graphene.
8. The preparation method according to claim 1, characterized in that: The plasma is generated by an arc furnace, a high frequency power supply, a laser, a radio frequency or a microwave.
9. The carbon-based supported nano manganese iron copper catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon-based supported nano manganese iron copper catalyst according to claim 9 in catalytic degradation of malodorous organic waste gas.
Citation Information
Patent Citations
Preparation method of supported ferric activated carbons as well as condition and device applying supported ferric activated carbons to absorb methylbenzene
CN104815614A
Mn-Fe double metal-doped active carbon-based desulfurization catalyst, and preparation method thereof
CN105107521A